2021
DOI: 10.23960/jsl.v9i3.532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strands Pre-treatment and Adhesive Type on the Properties of Oriented Strand Board Made from Gmelina (Gmelina arborea) Wood

Abstract: The objective of this study was to evaluate the effects of steam treatment of strands on the physical and mechanical properties of oriented strand board (OSB) from gmelina wood (Gmelina arborea) bonded with two types of adhesive. Strands of gmelina wood were steamed at 126°C and pressure of 0.14 MPa for 1 h. OSBs were prepared with a 0.6 g/cm3 target density using two types of adhesives, namely methylene diphenyl diisocyanate (MDI) and phenol-formaldehyde (PF) resins. The resin content used was 5% for MDI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Moreover, the choice of adhesive impacted the WA value. For example, the hydrophobic properties of MDI adhesive result in a board that absorbs less water, thus leading to reduced WA (Adrin et al 2013;Aisyah et al 2021). Before exposure, the BOSB had a higher TS than a BOSB exposed for 1 month.…”
Section: Water Absorption and Thickness Swellingmentioning
confidence: 99%
“…Moreover, the choice of adhesive impacted the WA value. For example, the hydrophobic properties of MDI adhesive result in a board that absorbs less water, thus leading to reduced WA (Adrin et al 2013;Aisyah et al 2021). Before exposure, the BOSB had a higher TS than a BOSB exposed for 1 month.…”
Section: Water Absorption and Thickness Swellingmentioning
confidence: 99%
“…In addition, the fact that the outer surface of the bamboo skin contains silica while the inner surface contains wax can reduce the adhesive strength (Nugroho and Ando 2000). Aisyah et al (2021) reported that the IB strength of OSB with isocyanate adhesive without steam treatment has lower than with steam treatment. Our study conducted that the manufacturer of flattened bamboo did not clean the outer and inner surfaces of the bamboo before it was made into boards.…”
Section: Internal Bonding Strengthmentioning
confidence: 99%
“…One type of adhesive that is compatible with CLT is polyurethane (PU). The application of PU-based adhesives to CLT resulted in a lower delamination percentage than CLT with epoxy and phenol resorcinol formaldehyde adhesives, as well as better mechanical properties than CLT with emulsion polymer isocyanate, epoxy, and phenol resorcinol formaldehyde adhesives (Aisyah et al 2021;Baskara et al 2022;Hariz et al 2021;Zelinka et al 2019). In addition, PU is also indicated to be low in emissions in its use as an exterior adhesive (Liang et al 2021).…”
Section: Introductionmentioning
confidence: 96%